An Action Recognition Scheme Using Fuzzy Log-Polar Histogram and Temporal Self-Similarity. (16th January 2011) - Sadek Sadek, Samy Samy; Al-Hamadi Al-Hamadi, Ayoub Ayoub; Michaelis Michaelis, Bernd Bernd; Sayed Sayed, Usama Usama
Abstract : Temporal shape variations intuitively appear to provide a good cue for human activity modeling. In this paper, we lay out a novel framework for human action recognition based on fuzzy log-polar histograms and temporal self-similarities. At first, a set of reliable keypoints are extracted from a video clip (i.e., action snippet). The local descriptors characterizing the temporal shape variations of action are then obtained by using the temporal self-similarities defined on the fuzzy log-polar histograms. Finally, the SVM classifier is trained on these features to realize the action recognition model. The proposed method is validated on two popular and publicly available action datasets. The results obtained are quite encouraging and show that an accuracy comparable or superior to that of the state-of-the-art is achievable. Furthermore, the method runs in real time and thus can offer timing guarantees to real-time applications.